2015
DOI: 10.1021/acs.jpca.5b00616
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Hydrated Methylamine: Structural Characteristics and H2N···H–O Hydrogen Bonds

Abstract: Methylamine is the simplest aliphatic amine found in human urine, blood, and tissues. It is thought to play a significant part in central nervous system disturbances observed during renal and hepatic disease. In this work we have investigated the methylamine hydration clusters using a basin hopping (BH) algorithm with the density functional theory (DFT). The results presented herein yield a detailed understanding of the structure and stability for a system consisting of one methylamine molecule and up to seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…Moreover, we observed the primary amine group bounded to a small number of water molecules, especially at the interface. This small coordination number is also consistent with recently proposed electronic structure calculations for hydrated MA in small water clusters 64 and on similar studies on surface-bound state for ammonia. 69 Nevertheless, the solute-solvent interaction appears to not be the only factor favoring the surface preference.…”
Section: E Hydrogen Bonding Network Surrounding Masupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we observed the primary amine group bounded to a small number of water molecules, especially at the interface. This small coordination number is also consistent with recently proposed electronic structure calculations for hydrated MA in small water clusters 64 and on similar studies on surface-bound state for ammonia. 69 Nevertheless, the solute-solvent interaction appears to not be the only factor favoring the surface preference.…”
Section: E Hydrogen Bonding Network Surrounding Masupporting
confidence: 92%
“…Figure 9 reports some typical configurations with different number of water hydrogen bond donors and acceptors toward the primary amine group. It is interesting to connect this figure with the optimized geometries for MA solvated in small water clusters (up to 5 water molecules) obtained by recent electronic structure calculations of Sha-Sha et al 64 According to Sha-Sha et al the most stable geometries were tetramer and pentamer water clusters with MA located outside the water ring and the nitrogen atom both donating and accepting one hydrogen bond. Since the 1D-1A configuration is the most common configuration at the interface, this observation provides a further molecular explanation for the surface preference of MA.…”
Section: E Hydrogen Bonding Network Surrounding Mamentioning
confidence: 82%
“…We found that water binds the nitrogen center most favorably with an interaction energy of −7.5 as compared to −5.2 kcal/mol of water‐water binding energy. The red shift of the vibrational frequencies of the elongated proton donating H−O bond, and the shortening of the N…H intermolecular distance with the addition of water molecules to the hydrated cluster were also observed from an ab initio simulation study . These tendencies were not found for the hydrated cluster containing five water molecules.…”
Section: Resultsmentioning
confidence: 76%
“…Ultimately, they have concluded that there was no proton transfer in the most stable geometry. Sha‐Sha et al . reported from DFT calculations that with the increase in size of methylamine‐water cluster, the strength of the H 2 N…H 2 O hydrogen bonds increase.…”
Section: Introductionmentioning
confidence: 99%
“…It is certain that sulfuric acid is a key component [2], but another stabilizing compound is required to explain observed new particle formation rates [3,4]. The predominantly investigated stabilizers are bases such as ammonia [5][6][7][8][9][10][11][12] and monoamines [13][14][15][16][17][18][19][20][21][22][23]. Amines have been shown to have an especially strong interaction with sulfuric acid, with a few ppt of dimethylamine yielding new particle formation rates of up to three orders of magnitude higher than ammonia [24].…”
Section: Introductionmentioning
confidence: 99%